Enhancing access to underutilized ground water potential for improving livelihoods and conflict reduction in Kagera Sub-Basin, Tanzania - Estella Mgala; Joel Nobert; Edmund B. Mabhuye; Brown Gwambene (Frontiers in Water)
Groundwater is a crucial resource for global populations and economies, particularly in developing countries where water scarcity is a growing concern. Serving as a primary water supply for approximately two billion people, it accounts for 42% of irrigation water and contributes to around 40% of global food production. However, groundwater sources still need to be explored due to differentiated water access, inadequate knowledge, poor technology, socio-economic challenges, and increasing pollution. This study focuses on the underutilized groundwater sources in the North West Highlands of Tanzania, where governance information is sparse in the existing literature. The study employed a mixed-methods approach, utilizing key informant interviews, household questionnaires, focus group discussions, direct observations, and secondary data sources. Results revealed that farming remains the dominant livelihood activity, with significant reliance on diverse water sources, yet water quality and availability are declining exacerbating the challenges. Despite ground water potential, disparities in knowledge, infrastructure development, technological capacity, and enforcement abilities significantly influenced its access. Concurrently, differing priorities among government actors hinder the optimal exploitation of groundwater to improve water access, exacerbating issues of water rights and conflicts. Most households access groundwater through inexpensive, simple technologies requiring minimal financial investment. The challenges such as declining water tables, well deepening and enlargement costs, limited financial resources, inadequate technology, and weak governance impede effective utilization. The study concludes that although groundwater utilization is currently low, it holds substantial potential for irrigation and improving water resilience, thereby reducing water rights conflicts. Under the changing climate and increasing demands, groundwater remains a promising resource for irrigation, enhancing water resilience and pursuit of Sustainable Development Goals (SDGs). Recommendations emphasize the need for understanding of water processes, improved access and quality to mitigate water conflicts. The findings are useful in informing policy-making, planners and guiding interventions aimed at enhancing the resilience of rural communities in the face of climate variability and water scarcity.